Engineering economics and engineering economics education strategy - T. Yu. Krotenko (Вестник университета)
Acceleration of scientific and technological progress requires a new approach to the training and retraining of talent engaged in the real sector of the economy, which is particularly true of the economy’s elite – engineering personnel. Globalization imposes new requirements with regard to the quality of modern engineers’ education. Russian engineers are confronted with the task of carrying out technological modernisation of the industry and entering new markets with new high-tech products. This necessitates a conceptualization of the cultural traditions, philosophical and historical foundations of modern engineering education, which makes the need to create a new type of educational environment extremely obvious. The article substantiates the creation and implementation of a new strategy for continuous engineering education based on transdisciplinarity and the combination of engineering education with economic and linguistic knowledge as well as knowledge in the field of information technology.